Morphine directly promotes thrombus formation in murine models of vascular thrombosis: A call for revisiting basic tenets. Issue 193 (September 2020) - Abu Fanne, Rami; Maraga, Emad; Meisel, Simcha Ron; Maanit, Shapira; Abdeen, Suhair; Roguin, Ariel; Higazi, Abd-Alroof
Highlights: Morphine is the analgesic drug of choice in acute ST-elevation myocardial infarction. A plausible direct effect of morphine on thrombus generation was investigated. Morphine promotes venous and arterial thrombosis through enhancing both platelet adhesion and contact pathway activation. In case morphine use is inevitable, upstream Glycoprotein IIb/IIIa antagonist loading is mandatory.